PENGEMBANGAN MEDIA PEMBELAJARAN IPS MENGGUNAKAN SPARKOL VIDEOSCRIBE TEMA KEGIATAN EKONOMI SISWA KELAS VII DI MTS MA’ARIF NU 14 SIDOREJO - Anita Anita; Triani Ratnawuri (UNIVERSITAS MUHAMMADIYAH METRO, 2019)
The purpose of this research is to produce IPS learning media using sparkol videoscribe which is valid, practical and effective to meet students' need. IPS learning media will then be tested feasibility by experts. This research uses the research procedure and development model of ADDIE. This development model consists of 5 development stages namely Analisys, Design, Development, Implementation, and Evaluation. The results showed that IPS learning media using sparkol videoscribe is feasible to use in learning. This is demonstrated by the results of the expert test on the display design of sparkol videoscribe learning media included into the criteria